2013
DOI: 10.1016/j.expneurol.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin converting enzyme inhibitor captopril protects nigrostriatal dopamine neurons in animal models of parkinsonism

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by a prominent loss of nigrostriatal dopamine (DA) neurons with an accompanying neuroinflammation. The peptide angiotensin II (AngII) plays a role in oxidative-stress induced disorders and is thought to mediate its detrimental actions via activation of AngII AT1 receptors. The brain renin-angiotensin system is implicated in neurodegenerative disorders including PD. Blockade of the angiotensin converting enzyme or AT1 receptors p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 61 publications
4
50
0
1
Order By: Relevance
“…Several lines of evidence suggested a potential association of Ang II/AT1R axis with the progression of PD, since a significantly higher level of Ang II in the CSF or brain tissues was observed in PD animal models as well as patients with this disease [13, 14]. Here, in support of these findings, we showed that the level of Ang II in the SN was obviously elevated in a rotenone-induced rat model of PD.…”
Section: Discussionsupporting
confidence: 87%
“…Several lines of evidence suggested a potential association of Ang II/AT1R axis with the progression of PD, since a significantly higher level of Ang II in the CSF or brain tissues was observed in PD animal models as well as patients with this disease [13, 14]. Here, in support of these findings, we showed that the level of Ang II in the SN was obviously elevated in a rotenone-induced rat model of PD.…”
Section: Discussionsupporting
confidence: 87%
“…Experimental data also support the involvement of brain RAS in dopaminergic degeneration [110,111,112]. It was demonstrated that AII increased the neurotoxic effect induced by low doses of 6-OHDA, and the treatment with inhibitors of ACE [113,114,112] or blockage of AT1Rs [98,95,96] resulted in a significant reduction of both the loss of dopaminergic neurons and the levels of protein oxidation and lipid peroxidation induced by the neurotoxins [115]. Furthermore antagonist of AT1Rs has been shown to be neuroprotective [116].…”
Section: Renin-angiotensin Systemmentioning
confidence: 79%
“…We have synthesised a nonapeptide, H-Pro-Pro-Thr-Thr-Thr-Lys-Phe-Ala-Ala-OH, which was named acein, which binds with high affinity and specificity to brain membranes of guinea pigs and rats. Acein binding sites were mainly localized in the dorsal striatum and substantia nigra areas of brain, where membrane-bound ACE is largely found (Zhuo et al, 1998;Sonsalla et al, 2013;Labandeira-Garcia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%